Questioning in the EFL Classroom: Teachers' and Students' Perspectives - Rizqa Fajria; Zulfadli Abdul Aziz; Muhammad Aulia (AT-TA'LIM, 2024)
Interaction is one crucial aspect that should occur between teacher and student to achieve learning objectives. Asking questions is one of the ways to get to the interaction. The interaction between teachers and students in the classroom, therefore, needs to examine. This qualitative research aims to analyze teachers' and students’ perspectives on teachers’ questioning. The purpose of this study is to know teachers’ and students’ perspectives on teachers’ questioning in the classroom. The result of this study was analyzed descriptively, and the data were collected by interviewing three teachers and eight students at an Islamic Junior High School in Banda Aceh. Based on the finding of the result, it showed that the teachers and students believe that teachers’ questions are important because teachers’ questions help teachers check their students understanding, motivate students in speaking practice, and motivate students in learning. The findings of this research help teachers realize that teachers' questions are important, so the teachers can use a proper type of questioning in the classroom. Furthermore, the teachers can build more interaction and help students to get more understanding and critical thinking. Finally, the researcher offers some implications and recommendations derived from this study. First, recommend that the teacher ask more high-order questioning in the classroom. Second, employing questioning strategies throughout the entire lesson. The third, paying attention to all students.